New approaches to strategic program-targeted management of Ukrainian construction sector innovation and economic development (Academic journal Industrial Machine Building Civil Engineering, 2020)
The situation analysis is carried out and the problems in the innovative and economic sphere of Ukraine development during its independence are revealed. Theoretical researches of modern tendencies, processes and procedures concerning progress organization and management of the leading countries and companies of the world are carried out. The model and algorithm of practical realization of this process are offered. The characteristic of structural and hierarchical construction of the strategic program-target management system of Ukraine progress and its elements is presented. The sequence of effective improvement of the public administration sustainable development system of the national economy and social life is determined. The practical implementation of the proposals outlined in this paper will help accelerate Ukraine's progress towards global economic standards
Keywords: construction sector; innovation and economic development; program-target management; strategic planning